Elevated Serum Pancreastatin Is an Indicator of Hepatic Metastasis in Patients With Small Bowel Neuroendocrine Tumors. Issue 7 (August 2016) - Khan, Tahsin M.; Garg, Malika; Warner, Richard R.P.; Uhr, Joshua H.; Divino, Celia M.
Abstract : Objectives: Serum pancreastatin is a sensitive and specific diagnostic biomarker in neuroendocrine tumors (NETs). Elevated pancreastatin levels are associated with worse progression-free survival and overall survival in small bowel and pancreatic NETs. In this study, we investigated the clinical significance of elevated serum pancreastatin in identifying metastatic disease to the liver. Methods: Retrospective chart review of patients with NET managed at a single institution was performed. The site of primary tumor, laboratory data, and presence of metastatic disease were reviewed. The sensitivity, specificity, and positive and negative predictive values for pancreastatin as indicator of liver metastasis were ascertained. Results: Data were abstracted from 77 patient records. Small bowel was the primary tumor site in 44 patients (57%), and 49 patients had metastasis to the liver (64%). Sensitivity and specificity of serum pancreastatin was 85.7% and 66.7%, respectively, which compared with 61.5% and 43.8% for chromogranin A, in identifying liver metastasis in patients with primary tumors of the small bowel. Conclusions: Elevated serum pancreastatin is a sensitive and specific assay for detecting the incidence of liver metastasis in patients with small-bowel NET. Routine measurement of pancreastatin in patients with NET, especially in patients with small bowel primaries, is supported.